2015
DOI: 10.1007/s10096-015-2369-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the APE2 gene expression level in Candida albicans clinical isolates from patients with diagnosed fungal infections

Abstract: The production of hydrolytic enzymes is considered a key virulence determinant of Candida albicans. Aminopeptidase 2 (Ape2) facilitates the penetration of C. albicans into the host tissue, by providing free amino acids to support fungal growth and proliferation. The objective of this study was to estimate the APE2 expression profile in C. albicans cells during invasion of the human epithelium. Sixty-one clinical fungal isolates and five reference strains were included in this study. The wild-type APE2 sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…RT-PCR analysis of a mixture of cDNA, ultra SYBR mixture (with ROX) (CWBiotech), and gene primers was performed in triplicate, with ACT1 was used as the endogenous control gene (Staniszewska et al 2015). RT-PCR was performed by using an ABI ViiA 7 (Applied Biosystems) sequence detection system for three separate experiments.…”
Section: R a F Tmentioning
confidence: 99%
“…RT-PCR analysis of a mixture of cDNA, ultra SYBR mixture (with ROX) (CWBiotech), and gene primers was performed in triplicate, with ACT1 was used as the endogenous control gene (Staniszewska et al 2015). RT-PCR was performed by using an ABI ViiA 7 (Applied Biosystems) sequence detection system for three separate experiments.…”
Section: R a F Tmentioning
confidence: 99%
“…RT-PCR preparations were mixed with cDNA, ultra SYBR mixture (with ROX) (CWBiotech), and gene primers in triplicate. The ACT1 gene was used as the endogenous control (29). RT-PCRs were carried out with an ABI ViiA 7 (Applied Biosystems) sequence detection system using SYBR green I (CWBiotech) in duplicate for three separate experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The C. albicans adhesion protein might further help with adhesion and escape from macrophages. Upregulation of some proteases (Ape2 [ 65 ], orf19.1891, and orf19.7263) suggested that proteolysis and peptide utilization were necessary for C. albicans survival. Some upregulated proteins (orf19.4914.1, orf19.4441, orf19.5201.1, orf19.6035, orf19.357, orf19.3053, and orf19.5078) related to unknown proteins or hyphal formation were not functionally characterized in detail.…”
Section: Mixed and Quantitative Proteome Analysismentioning
confidence: 99%